2012
DOI: 10.1089/dia.2011.0303
|View full text |Cite
|
Sign up to set email alerts
|

Can a Tool That Automates Insulin Titration Be a Key to Diabetes Management?

Abstract: Background: Most patients who use insulin do not achieve optimal glycemic control and become susceptible to complications. Numerous clinical trials have shown that frequent insulin dosage titration is imperative to achieve glycemic control. Unfortunately, implementation of such a paradigm is often impractical. We hypothesized that the Diabetes Insulin Guidance System (DIGSÔ) (Hygieia, Inc., Ann Arbor, MI) software, which automatically advises patients on adjustment of insulin dosage, would provide safe and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…These studies were published between January 2010 and August 2015, and they evaluated a total of 8 mobile medical app products: Blue Star 8,9 Diabeo, 1012 Diabetes Diary, 13 DID, 14,15 Accu-Chek Aviva Expert, 16,17 Diabetes Insulin Guidance Systems, 18 FreeStyle InsulLinx, 19,20 and Telcare. 21 Six apps (Dexcom Share, Glooko, Accu-Chek Connect, Dario, Livongo, and Telcare) have received FDA clearance for use but do not have studies on efficacy and safety in peer-reviewed literature.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were published between January 2010 and August 2015, and they evaluated a total of 8 mobile medical app products: Blue Star 8,9 Diabeo, 1012 Diabetes Diary, 13 DID, 14,15 Accu-Chek Aviva Expert, 16,17 Diabetes Insulin Guidance Systems, 18 FreeStyle InsulLinx, 19,20 and Telcare. 21 Six apps (Dexcom Share, Glooko, Accu-Chek Connect, Dario, Livongo, and Telcare) have received FDA clearance for use but do not have studies on efficacy and safety in peer-reviewed literature.…”
Section: Introductionmentioning
confidence: 99%
“…A feasibility study with a learning algorithm showed improvement in HbA1c, mean glucose level, and hypoglycemia. 11 Future studies should also include assessments of adherence and additional reasons for heterogeneity in results such as the inclusion of bolus reminders along with the bolus calculator in some of the RCTs but not in all.…”
Section: Diabetes Technology and Therapeuticsmentioning
confidence: 99%
“…Clearly these systems, which require further evaluation, can help patients, especially those with poor numeracy; however, they cannot overcome the more serious issue of acceptance by patients of their disease. patients with type 2 diabetes on basal-bolus therapy, and (3) patients with type 2 diabetes treated with twice-daily biphasic insulin [14]. During the 12-week intervention period, DIGS processed patients' glucose readings and provided insulin dosage adjustments on a weekly basis.…”
Section: Second Level: Automated Bolus Calculatorsmentioning
confidence: 99%